Pragmatic strategies and linguistic structures in making 'suggestions': towards comprehensive taxonomies - Abolfathiasl, Hossein; Abdullah, Ain Nadzimah (Australian International Academic Centre, 2013)
This paper analyses and upgrades taxonomies of strategies and structures for the speech act of suggesting based on existing taxonomies and classifications in the pragmatics research literature. Previous studies have focused mainly on linguistic structures used to perform the speech act of suggesting. Thus, there seems to be a need to provide a more comprehensive set of taxonomies for structures as well as strategies that can be used in EFL/ESL classrooms and for research on the speech act of suggesting. To this end, the speech act of suggesting is defined first and the features of this speech act are discussed. Second, the most recent classifications proposed for structures and linguistic realization strategies for suggestions were analysed and contrasted and a more comprehensive taxonomy of structures and linguistic realization strategies is provided, based on previous taxonomies. Finally, taxonomy of politeness strategies in making suggestions are provided, based on recent studies in cross-cultural pragmatics research.